Analisis Strategi Pemasaran untuk Meningkatkan Daya Saing UMKM (Studi Kasus Pada Jasa Desain Perspektif Malang) - Putra, Moch. Gilang Aryana; Lestari, Hari Budi; Tohari, Nursyamsida (Program Studi Akuntansi Fakultas Ekonomi Universitas PGRI Argopuro Jember, 2024)
This study aims to get an overview of the marketing strategy used by Jasa Desain Perspektif Malang to increase sales. Marketing strategy is one way to win sustainable competitive advantage for companies that produce goods or services. Marketing strategy can be seen as one of the bases used in compiling overall corporate planning. Data collection techniques are carried out by documentation and observation. The results of the study concluded that the marketing strategy of Jasa Desain Perspektif Malang uses (1) market segmentation strategy; (2) target market determination strategy (targeting); (3) market positioning strategy (positioning); and (4) marketing mix. Based on this marketing strategy, there is an increase in total sales and is used as a reference for the effectiveness of marketing strategies in competition between Desain Perspektif Malang businesses.